Pemberdayaan Peternak Sapi Perah Melalui Diversifikasi Produk Olahan Susu di Dukuh Krajan Desa Bedrug - Annisa Nur Laili; Teguh Ansori (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Dukuh Krajan, Bedrug Village, is located in Pulung District, Ponorogo Regency. Most of the population work as farmers and dairy farmers. The productivity of cow’s milk is around ten to fifteen liters for one cow that is not lactating, while a cow that is breastfeeding is around eighteen to twenty liters every day. Where in Dukuh Krajan, Bedrug Village has many dairy farmers, namely around forty dairy cows that can be used to process milk into several flavors, The problem faced by cattle breeders in Dukuh Krajan, Bedrug Village, is that they always follow the price of collectors, where the selling price of cow’s milk is unstable. Breeders only get a selling price of Rp. 7.600,00 or Rp. 10.000,00 for each liter. The purpose of this service is the opportunity to empower dairy farmer through processing milk into several flavors. The service method used is Asset Based Community Development (ABCD). The results of this research are to produce products, bussines ideas and community creativity through the utilization of cow’s milk processing into several flavors that have better tastes and higher economic value because they provide alternative flavors for buyers, thereby increasing the activities of the Dukuh Krajan community in Bedrug Village.